2018
DOI: 10.1142/s0219199717500390
|View full text |Cite
|
Sign up to set email alerts
|

e-Symmetric rings

Abstract: Let [Formula: see text] be a ring and [Formula: see text] an idempotent of [Formula: see text], [Formula: see text] is called an [Formula: see text]-symmetric ring if [Formula: see text] implies [Formula: see text] for all [Formula: see text]. Obviously, [Formula: see text] is a symmetric ring if and only if [Formula: see text] is a [Formula: see text]-symmetric ring. In this paper, we show that a ring [Formula: see text] is [Formula: see text]-symmetric if and only if [Formula: see text] is left semicentral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…In [13] e-symmetric rings and e-reduced rings are introduced and investigated. Let R be a ring and e 2 = e ∈ R. Then R is called e-symmetric if whenever abc = 0, then acbe = 0 for every a, b, c ∈ R. The ring R is right (resp.…”
Section: Properties Of E-semicommutative Ringsmentioning
confidence: 99%
See 3 more Smart Citations
“…In [13] e-symmetric rings and e-reduced rings are introduced and investigated. Let R be a ring and e 2 = e ∈ R. Then R is called e-symmetric if whenever abc = 0, then acbe = 0 for every a, b, c ∈ R. The ring R is right (resp.…”
Section: Properties Of E-semicommutative Ringsmentioning
confidence: 99%
“…left) e-reduced if ae = 0 (resp. ea = 0) for each nilpotent a ∈ R. By motivated these e-contexts, in that vein, in this section we will introduce and study the structures of right e-semicommutative rings generalizing e-symmetric rings and right e-reduced rings [13]. Throughout this paper, e denotes an idempotent element of a ring R which is under consideration.…”
Section: Properties Of E-semicommutative Ringsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [11], Wei introduced generalized weakly symmetric rings, which further generalized the concept of symmetric rings. In [7], a ring R is called (strongly) e -symmetric if for any a, b, c ∈ R , abc = 0 implies (aceb = 0 ) acbe = 0 , where e ∈ E(R) . It is shown that a ring R is e -symmetric if and only if e is left semicentral and eRe is symmetric [7,Theorem 2.2].…”
Section: Introductionmentioning
confidence: 99%